PUNISHMENT PATTERN IN ISLAMIC BOARDING SCHOOL - Nurbuana Gofar (Conciencia, 2020)
The purpose of this study is to provide an overview of the pattern of punishment in Islamic boarding schools and the educators reason in applying this method for students who commit violations. One of the places of study for students, boarding school, also included a residence for students who are used to their religious activities like praying, reciting of holy Qur'an, studying the holy yellow books, and fiqh. In addition, Islamic boarding school also teaches other general sciences and has a big role in directing and shaping student personality for the better, as well as creating reliable graduates who are able to compete in this advanced age. Therefore, everything can be achieved definitely that it can not be separated from the methods used, in this case, is punishment. The punishment given to students in Islamic boarding schools is as feedback who commits violations therefore they will not repeat their mistakes. Although sometimes it gives a bad impression and was considered less relevant, however, the discussion of punishment is one of the important things to be discussed in detail to achieve good behavior. This study was used in qualitative data. The data used in this study was a primer data that was an interview through a key informant and a student guidance book which discussed student discipline and violations of Islamic students in Al-Itifaqiyah boarding school, and the secondary data were books, articles, journal, and other literature which was relevant with discussion. This study produced that the punishment given to students who had done mistake and violence the students' rules had fulfilled the condition and criteria. The result of this study was supported by Abdullah Nasih Ulwan's opinion that a teacher must take a look at the conditions of punishment usage and through the processes and it was adapted by conditions.